More durable or more vulnerable? – Effect of nanoparticles on long-term performance of polymeric nanocomposites during UV exposure. (1st January 2012) - Gu, Xiaohong; Zhe, Dongmei; Zhao, Minhua; Chen, Guodong; Watson, Stephanie. S.; Stutzman, Paul E.; Nguyen, Tinh; Chin, Joannie W.; Martin, Jonathan W.
ZnO nanoparticle is being used as an inorganic UV absorber for polymers. However, the mechanism of how ZnO nanoparticles influence the photo degradation of polymersis is not well understood. This study has investigated the role of ZnO nanoparticles in the long-term performance of a polyurethane (PU) nanocomposite subject to UV radiation. PU samples containing different levels of ZnO nanoparticles were exposed to the NIST S imulated Photodegradation via High Energy Radiant Exposure (SPHERE) UV chamber under both dry (0% RH) and moist (75% RH) conditions at 45°C. Chemical and physical properties with exposure times were characterised using multiple spectroscopic and microscopic techniques. The results indicated that the studied ZnO nanoparticles acted as a catalyst and accelerated the photodegradation of PU. The photo-catalytic effect was dependent on ZnO concentration and RH. It is suggested that systematical long-term performance study under different exposure environments is important for correctly evaluating the role of nanoparticles on durability and sustainability of polymer nanocomposites.